A Double Difference Tomography Study of the Washington Forearc: Does Siletzia Control Crustal Seismicity?. Issue 10 (3rd October 2020) - Merrill, R.; Bostock, M. G.; Peacock, S. M.; Calvert, A. J.; Christensen, N. I.
Abstract: We present new seismic tomography of the Washington forearc using a suite of manually picked regional earthquake phase arrivals. The recovery of similarly sampled P and S velocity permits the robust calculation of Poisson's ratio throughout the region. The seismological signature of Siletzia, an accreted oceanic plateau that crops out in Washington as the Crescent Formation, is evident in our models as a continuous high Poisson's ratio body that coincides with subsurface structures estimated from potential field maps. Relocated earthquakes preferentially locate in low Poisson's ratio regions in the forearc crust and, in particular, in a diffuse layer located at 15–25 km depth in the crust beneath relatively aseismic Siletzia. Our imaging of the Puget Sound is consistent with previous interpretations of the architecture of major faults and blocks, as evident by distinct Poisson's ratio signatures that distinguish sedimentary basins from mafic rocks of the Crescent Formation. We speculate that seismicity below the Puget Sound is promoted by slab‐derived fluids that are localized beneath Siletzia as a result of intrinsic low vertical permeability. Key Points: We determine similarly sampled P and S velocity models for western Washington and southern Vancouver Island, enabling the determination of Poisson's ratio throughout the region Siletzia, an accreted oceanic plateau, is imaged as a continuous high Poisson's ratio body in the forearc that thins to the north Relocated seismicity preferentially locates within low Poisson's ratio regions, whereas Siletzia is relatively aseismic